Impact of Zakat-Based Business Capital on Mustahiq's Welfare Post-Disaster in Sigi Regency - Uswatun Hasanah; Syamsul Anwar; Misnen Ardiansyah (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This study investigates the BAZNAS Microfinance Desa (BMD) Sigi program’s impacts on the material and spiritual well-being of the Mustahiq (zakat beneficiaries). The quantitative CIBEST model and qualitative observation were performed on 100 households recruited using a random sampling technique. The results show that BMD Sigi’s program positively impacted Mustahiq’s material and spiritual well-being, with increases of 35.39% and 10%, respectively. The welfare index rose 19%, and the material poverty index fell by 1%. Both spiritual poverty and the absolute index fell by 6% and 12%, respectively. Our direct observation further supports the quantitative findings, showing that monitoring and technical support provided by BMD Sigi is crucial for the successful implementation of the program. This study contributes to the novelty of measuring the impact of zakat distribution on productive means using quantitative and qualitative approaches with particular evidence from a post-disaster area.JEL Classification: D64, I38, L31, Z12How to Cite:Hasanah, U., Anwar, S., & Ardiansyah, M. (2023). Impact of Zakat-Based Business Capital on Mustahiq’s Welfare Post-Disaster in Sigi Regency. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 175-190. https://doi.org/10.15408/sjie.v12i1.25178.